Foreign Language Influence on Financial Literacy and Risk Behavior among High School Students - Rizal, Moch. Deni; Dewi, Maria Rosa Kumala; Mariani, Melania Lulut (LifeSciFi, 2025)
Financial literacy is an essential skill for the 21st century, yet understanding is often limited, especially when delivered in a foreign language. This study aims to examine the impact of foreign language on risk taking, financial attitudes and behavior of High School Students in Surakarta, with a focus on risk taking values, financial attitudes, and financial behavior. The research is conducted in two stages: the first stage conceptualizes the influence of teaching media (TM) and the native language on risk-taking, while the second stage analyzes its impact on financial attitudes and behaviors. The results show that both the use of English and the native language significantly affect students' risk-taking values, which in turn influence their financial attitudes and behaviors. These findings support the Foreign Language Effect theory, which suggests that foreign language can reduce emotional bias and facilitate more rational decision-making. This study highlights the importance of bilingual financial literacy education that considers the influence of language and culture in enhancing financial risk understanding and making more informed financial decisions.